BLOG 2.0: a software system for character‐based species classification with DNA Barcode sequences. What it does, how to use it. (28th January 2013) - Weitschek, Emanuel; Van, Robin; Felici, Giovanni; Bertolazzi, Paola
Abstract BLOG (Barcoding with LOGic) is a diagnostic and character‐based DNA Barcode analysis method. Its aim is to classify specimens to species based on DNA Barcode sequences and on a supervised machine learning approach, using classification rules that compactly characterize species in terms of DNA Barcode locations of key diagnostic nucleotides. The BLOG 2.0 software, its fundamental modules, online/offline user interfaces and recent improvements are described. These improvements affect both methodology and software design, and lead to the availability of different releases on the website http://dmb.iasi.cnr.it/blog-downloads.php. Previous and new experimental tests show that BLOG 2.0 outperforms previous versions as well as other DNA Barcode analysis methods.